THE USE OF POROUS CERAMICS FOR EVAPORATIVE AND EVAPORATIVE – VAPOR –COMPRESSION SYSTEMS - Cheban D.N.; Doroshenko A.V. (Problems of the Regional Energetics, 2013)
The use of natural evaporative cooling is one of technical solutions of problem of energy efficiency in air conditioning systems. The use of evaporative cooling in the first combined cooling stage allows reducing the load on the condenser of the cooling machine due to reducing of the condensing temperature. This combination allows the use of this type of system in any climatic conditions, including regions with small water resources. Multi-porous ceramic structure is used in evaporative air coolers and water coolers in this case. The objective of this paper is to show advantages of the using of porous ceramic as a working attachment, and to show advantages of the proposed scheme of compression-evaporation systems in comparison with standard vapor compression systems. Experimental research proved the fact, that in the film mode cooling efficiency of air flow is between EA=0,6÷0,7 and is slightly dependent of water flow. For countries with hot and dry climate where reserves of water are limited, it is recommended to use cyclical regime with EA≈0,65 value, or to use channel regime with a value of EA≈0,55. This leads to considerable energy savings. It has been determined, that combined air conditioning system is completely closed on the consumption of water at the parameters of the outside air equal to tA =32ºC and XA>13g/kg (in system with direct evaporative cooling machine), and tA=32ºC and XA>12g/kg (in system with indirect evaporative cooling machine). With these parameters, the cost of water in evaporative cooling stage can be fully compensated by condensate from the evaporator chiller.